Review on Economic Importance's of Rabies in Developing Countries and Its Controls - Gemechu Regea (Archives of Preventive Medicine - Peertechz Publications, 2017)
Rabies is a zoonotic viral disease of mammals most often transmitted through the bite of a rabid animal. Warm blooded animals are susceptible to infection with rabies virus and are therefore possible reservoirs. Dogs are the main reservoir of rabies virus in developing countries and are responsible for 99% of human infections. Even though developed countries have been able to contain recent outbreaks of zoonotic diseases, many resource-limited and transitioning countries have not been able to react adequately. Rabies remains a global zoonosis of major public health, agricultural and economic significance. It cause many economic loses in many developing country. Rabies transmitted by dogs is responsible for the loss of over 1.8 million DALYs (disability adjusted life years) every year, with direct and indirect economic costs (PEP, animal tests, dog vaccination, and livestock losses) totaling $5.5 billion per year. In addition to that its effects also included the costs associated with the risk of human mortality, resulted in a global cost for canine rabies of $120 billion. These virus disease result in about 24,000 to 60,000 deaths worldwide per year. More than 95% of human deaths caused by rabies occur in Africa and Asia. For instance thousands of people are infected with rabies in Ethiopia, and an estimated 2,700 people die each year-one of the highest rates in the world. Even though total number of animal burden is unknown, but healthcare workers and scientists confirmed thousands of cases of rabies in dogs in Addis Ababa (the country's capital) region alone. Rabies is present in more than 150 countries and on all continents but Antarctica. To mitigate those economic loss due to rabies, it is important to prevent through use of vaccine and environmental management.